Robust Controller With Least Mean Square Adaptive Filter for Voltage Source Inverters: Passivity-Based Design - Kenta Koiwa; Taiki Goto; Qingquan Liu; Kang-Zhi Liu; Tadanao Zanma (IEEE Access, 2025)
Voltage source inverters (VSIs) are essential for many applications. However, it is challenging to design a controller that enables a VSI to generate a sinusoidal load voltage with no steady-state error regardless of loads. Moreover, the controller has to suppress the harmonic distortion caused by a nonlinear load, such as a diode rectifier, while stabilizing the VSI. In this paper, we proposes a novel dual-loop controller for VSIs that comprises a passivity-based robust controller in the inner loop and a least mean square adaptive filter (LMS-AF) in the outer loop. The proposed controller can guarantee the robust stability for both linear and nonlinear loads, while achieving zero steady-state, fast-tracking, and robustness of the sensor noise. Regarding the harmonics caused by the diode rectifier load as cyclic, we suppress the harmonics caused by this load by applying the LMS-AF to the VSI controller. We demonstrate the effectiveness of the proposed controller through comparisons with conventional control approaches via simulations and experiments.